Analisis Kekuatan Daya Dukung Pondasi Helical Menggunakan Data Sondir Pada Tanah Gambut - Galang Maulana; Ferry Fatnanta; Muhardi Muhardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Bearing capacity of Helical Pile on peat soil can be obtained from cone penetration test (CPT). Bearing capacity based on CPT data is calculated by Bustamante & Gianeselli (LCPC) method, Schmertmann method, method Meyerhoff, Price & Wardle method, and Tumay & Fakhroo method. Meanwhile, there are two methods based on peat soil mechanisms to determine the bearing capacity of the helical pile such a cylindrical shear method and individual bearing method. This research evaluates bearing capacity of the five methods above by implementing two basic methods helical pile on peat soil that most closely to the actual bearing capacity. The results showed that the method Bustamante & Gianeselli (LCPC) to provide bearing capacity that most closely to the actual bearing capacity compared to other methods. Reduction factor is also necessary to modify bearing capacity the foundation Helical. After reduced, bearing capacity of each method has decreased significantly and tends to approach the actual bearing capacity.Keywords: Cone Penetration Test, Helical Foundation, Peat, Capability, Reduction Factor.